Iodine-123-meta-iodobenzylguanidine Myocardial Scintigraphy in Isolated Autonomic Failure: Potential Red Flag for Future Multiple System Atrophy - Baschieri, Francesca; Calandra-Buonaura, Giovanna; Cecere, Annagrazia; Barletta, Giorgio; Contin, Manuela; Parchi, Piero; Cortelli, Pietro (Frontiers in Neurology, 2017)
Pure autonomic failure (PAF) is challenging as it can be the presenting feature of a central nervous system syncleinopathy such as Parkinson’s disease (PD) or Multiple System Atrophy (MSA). Because the prognosis of MSA and PD is so different, predictive features for a possible conversion can be extremely valuable. In this paper, we report three cases (two with autopsy-proven diagnosis) that had isolated AF for many years before converting to MSA or PD. Of all the tests that were performed during the pre-motor stage, MIBG myocardial scintigraphy was predictive of the conversion to MSA. We suggest that MIBG myocardial scintigraphy, when performed in patients with isolated AF, may be a valuable predictor of conversion to MSA. On the contrary, the role of such test in parkinsonian patients irrespective of the presence of AF is still to be clarified.